Lower serum insulin-like growth factor 2 level in patients with bipolar disorder is associated with the severity of manic symptoms during manic episodes - Ye, Shi-Yi; Zhao, Ying; Liu, Zhao-Bo; Luo, Cui-Pin; Xiong, Jian-Wen; Zhan, Jin-Qiong; Li, Yi-Heng; Wei, Bo; Chen, Chun-Nuan; Yang, Yuan-Jian (Frontiers in Psychiatry, 2024)
Objective Accumulating evidence has indicated that neurodevelopmental defects may underlie the pathophysiology of bipolar disorder (BD). Insulin-like growth factors (IGFs) are a family of neurotrophic factors that are essential for the survival and development of neurons. The present study aims to investigate whether IGF-2 signaling is implicated in the pathophysiological processes of BD. Method 50 healthy controls and 78 patients with BD, including 23 patients who diagnosed acute depressive episode and 55 patients who diagnosed acute manic episode, were recruited in this study. The 17-item Hamilton Depression Rating Scale (HAMD-17) and the Young Mania Rating Scale (YMRS) were used to assess the severity of the depressive and manic symptoms, respectively. The serum IGF-2 level was determined by an enzyme-linked immunosorbent assay (ELISA). The Kolmogorov-Smirnov and Mann-Whitney U tests were used for between-group comparisons and spearman analysis was used to analyze correlations. Results Patients with BD had lower serum IGF-2 levels (66.08 ± 21.22 ng/ml) when compared to healthy controls (88.72 ± 31.55 ng/ml). BD patients were divided into manic episode and depressive episode subgroups. We found that serum IGF-2 levels were reduced in both the mania and depression subgroups (mania: 67.19 ± 21.52 ng/ml, depression: 63.43 ± 20.67 ng/ml; P < 0.001), while no significant difference was observed between two groups (P > 0.05). Spearman correlation analyses revealed that the levels of serum IGF-2 were negatively correlated with the YMRS scores in BD patients (r = -0.522, P < 0.001). Furthermore, IGF-2 was found to be an independent contributor to the severity of symptoms in patients with manic episodes (B = -0.610, t = -5.299, P < 0.001). Conclusion Lower serum IGF-2 levels were found in BD patients and correlated with the severity of the manic symptoms in these patients during manic episodes. These results suggest that reduced IGF-2 levels might be involved in the pathophysiology of BD, and serum IGF-2 could be a peripheral biomarker for the evaluation of the severity of manic symptoms in BD patients.